Mental health indicators in women of migratory zones (Zacatecas) with or without an immigrant husband - Acevedo Sánchez, Carlos Ernesto (Consorcio de Universidades Mexicanas A.C., 2017)
The World Health Organization (WHO) recognizes that migration has become a public health problem; at the same time has degree the vulnerability of the women in the points of origin. For this reason the objective of this research was to know the prevalence of mental health indicators in women from migratory zones (Zacatecas) with migrant partner or not and to verify the protective effect of having a nonimmigrant partner. For this purpose the questionnaire: epidemiological profile of women with migrant partners in traditional and emergent areas with high migratory incidence in the state of Zacatecas, using the category of mental health indicators which is a Likert scale with an alpha of Cronbach of 0.897, a validity of 98.3%, a variance of 118,636 and a standard deviation of 10.89201 for a sample of 279 women from the municipalities of Jerez and Juan Aldama, of which 144 were women with nonimmigrant partners and 135 women with migrant couple. Trough statistical analyzes of hypothesis testing, independence, confidence intervals, contrast, statistics significance, and the value of r for both groups of women; finding that women with a migrant partner have a higher prevalence in the indicators of hostility and anxiety and the protective effect of having a nonimmigrant partner influences the indicators of depression, interpersonal sensitivity and somatization.